Depression and Anxiety among Tuberculosis Patients: A Systematic Review and Meta-analysis - Vikas Panibatla; Sharath Burugina Nagaraja; Deepa Mohan; Sreenath Menon Parambanattu Kizhakkethil; M. D. Sangeetha (Indian Journal of Social Psychiatry)
Background: Tuberculosis (TB) patients often experience depressive and anxiety symptoms, which can significantly impact their quality of life, treatment adherence, and outcomes. Understanding the magnitude of these mental health issues is crucial for improving TB programs and achieving successful treatment outcomes. Materials and Methods: We conducted a systematic review and meta-analysis, to assess the prevalence of depressive and anxiety symptoms among TB patients. Relevant studies were identified through a search of the PubMed database. Studies were assessed for quality using the Newcastle–Ottawa Quality Assessment Scale (NOS). Data extraction was performed, and a random-effects meta-analysis was conducted to estimate pooled prevalence rates. Results: Forty studies were included in the analysis. The pooled estimated prevalence of depression among TB patients was 11% (95% confidence interval [CI]: 11–12), while the pooled estimated prevalence of anxiety was 28% (95% CI: 26–29). Subgroup analyses revealed variations in the prevalence rates among drug-sensitive (DS-TB), drug-resistant, and extensively drug-resistant patients, as well as across continents and settings. Conclusions: The review indicates that there was a considerable burden of depressive and anxiety symptoms among TB patients worldwide. The findings emphasize the need for routine screening, integrated care approaches, and targeted interventions to address the mental health needs of TB patients.